ACL reconstruction with hamstring tendon autograft and accelerated brace-free rehabilitation: a systematic review of clinical outcomes. Issue 1 (9th April 2018) - Janssen, Rob P A; van Melick, Nicky; van Mourik, Jan B A; Reijman, Max; van Rhijn, Lodewijk W
Abstract : Objective: To investigate the clinical outcomes after hamstring tendon autograft ACL reconstruction (ACLR) with accelerated, brace-free rehabilitation. Design: Systematic review according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Data sources: Embase, MEDLINE Ovid, Web of Science, Cochrane CENTRAL and Google scholar from 1 January 1974 to 31 January 2017. Eligibility criteria for selecting studies: Study designs reporting outcomes in adults after arthroscopic, primary ACLR with hamstring autograft and accelerated, brace-free rehabilitation. Results: Twenty-four studies were included in the review. The clinical outcomes after hamstring tendon autograft ACLR with accelerated brace-free rehabilitation were the following: (1) early start of open kinetic exercises at 4 weeks in a limited range of motion (ROM, 90°−45°) and progressive concentric and eccentric exercises from 12 weeks did not alter outcomes, (2) gender and age did not influence clinical outcomes, (3) anatomical reconstructions showed better results than non-anatomical reconstructions, (4) there was no difference between single-bundle and double-bundle reconstructions, (5) femoral and tibial tunnel widening occurred, (6) hamstring tendons regenerated after harvest and (7) biological knowledge did not support return to sports at 4–6 months. Conclusions: After hamstring tendon autograft ACLR with accelerated brace-free rehabilitation, clinical outcome is similar after single-bundle and double-bundle ACLR. Early start of open kinetic exercises at 4 weeks in a limited ROM (90°−45°) and progressive concentric and eccentric exercises from 12 weeks postsurgery do not alter clinical outcome. Further research should focus on achievement of best balance between graft loading and graft healing in the various rehabilitation phases after ACLR as well as on validated, criterion-based assessments for safe return to sports. Level of evidence: Level 2b; therapeutic outcome studies.